LAW ENFORCEMENT OF CRIMINAL ACTIONS ABOUT NARCOTICS CLASS I IN THE CRIMINAL JUSTICE SYSTEM IN INDONESIA - Agha Hadi Saputra; Kristiawanto; Joko Sriwidodo; Ramlani Lina Sinaulan (Scholar Express Journals, 2023)
The research method used in this study is a normative juridical approach which is supported by empirical juridical by detailing the description, namely a research which deductively begins with an analysis of the articles in the laws and regulations governing the problem of law enforcement perpetrators of narcotics abuse of class I in Indonesian criminal justice system. In addition, primary data is also used to support secondary data on legal materials. The results of the study that the current criminal law enforcement in Indonesia, especially in special criminal laws or criminal legislation outside the criminal law code (KUHP), there is a tendency to use a double track system in the sanctions system which means that criminal sanctions and action sanctions are regulated at the same time. In the process of law enforcement against narcotics crimes, both in the process of investigation, investigation, prosecution, examination before a court hearing and the execution process refers to the Criminal Procedure Code (KUHAP) while the imposition of sanctions is regulated in Law Number 35 of 2009 concerning Narcotics. The form of sanctions against perpetrators of criminal acts of abuse of narcotics in the criminal justice system in Indonesia has been regulated in Law Number 35 of 2009 concerning Narcotics. The application of criminal sanctions to each of the perpetrators participating in the crime of narcotics abuse is not always the same between each perpetrator. However, the imposition of sanctions does not have to be in accordance with the demands of the prosecutor because the judge has the principle of freedom in deciding a case according to the existing legal rules and also the facts revealed in court.
Keywords: Law Enforcement; Narcotics Crime; Criminal Justice System